Optimized design and experiment of spiral-type intra-row weeding actuator for maize (Zea mays L.) planting - Jia, Honglei; Gu, Binglong; Ma, Zhongyang; Liu, Huili; Wang, Gang; Li, Mingwei; Tan, Hewen (International Journal of Agricultural and Biological Engineering, 2021)
Mechanical weeding not only avoids crop herbicide residue but also protects the ecological environment. Compared with mechanical inter-row weeding, mechanical intra-row weeding needs to avoid crop plants, which is conducive to causing a higher rate of seedling damage. In order to realize maize (Zea mays L.) intra-row weeding, a maize intra-row weeding mechanism was designed in this study. The mechanism can detect maize seedlings by infrared beam tube, then a sliding-cutting bevel tool moves spirally amid maize seedlings, so as to eradicate intra-row weeds. A field experiment was conducted under the following experimental conditions: the bevel tool rotation speed was 800-1400 r/min, the mechanism forward speed was 4-7 km/h, and the bevel tool depth was 2-14 cm, the experimental results illustrated that the mechanism’s average weeding rate and seedling damage rate were 95.8% and 0.6%, respectively. The variance analysis showed that the primary and secondary factors that affecting the weeding rate and seedling damage rate were the same, which were bevel tool rotation speed, mechanism forward speed, bevel tool depth in soil in a descending order according to the significances. The result of the field experiment may provide a reference for intra-row weeding device design. Keywords: optimization design, spiral forward, intra-row weeding actuator, maize planting DOI: 10.25165/j.ijabe.20211406.6542 Citation: Jia H L, Gu B L, Ma Z Y, Liu H L, Wang G, Li M W, et al. Optimized design and experiment of spiral-type intra-row weeding actuator for maize (Zea mays L.) planting. Int J Agric & Biol Eng, 2021; 14(6): 54–60.